EFEKTIVITAS PEMBELAJARAN DARING MELALUI APLIKASI WHATSAPP PADA MATA PELAJARAN TEMATIK DI MI NURUL ULUM ARJOSARI - Rizko Afriada; Muhamad Afifullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The implementation of online learning through the Whatsapp application on thematic subjects at MI Nurul Ulum Arjosari, the teacher carries out online learning in the Whatsapp group, learning time on thematic subjects is carried out on Mondays from 08.00-10.00 WIB and for task collection time is given until 00.00 night, as for the presence of the teacher using the collection of student assignments for proof of attendance. 2) the effectiveness of learning using the Whtasapp application, namely the teacher uses 4 foundations, namely, based on the minimum completeness criteria value, daily tests or task collection, mid-semester assessment, end-of-semester assessment, and can be concluded from the data that researchers get directly in using the Whatsapp application on thematic subjects is quite effective, although there are still shortcomings in this learning. 3) the advantages and disadvantages of using the WhatsApp application in thematic learning on the use of the Whatsapp application are as follows; Whatsapp is an application that is used by the people of Indonesia, it uses low quota, it can be used anywhere with the condition that there is a signal, as for the following shortcomings; have to use a signal, and there are limitations in transmitting video.